THE UTILITY OF CONTRAST-ENHANCED ULTRASONOGRAPHY IN DIAGNOSING CHILD'S VESICOURETERAL REFLUX - A CASE REPORT AND A REVIEW OF THE LITERATURE - Maria Oana Marginean; Carmen Duicu; Vladut Sasaran; Cristina Oana Marginean; Lorena Elena Melit (Amaltea Medical Publishing House, 2017)
Vesicoureteral reflux represents the reflow of bladder content in the ureter and pelvicalyceal system with their subsequent dilation. Most of the cases of urinary tract infections in child are associated with vesicoureteral reflux. We present the case of a 3-year-old female patient, with a history of multiple symptomatic urinary tract infections, who was admitted in our clinic for specialty investigations and establishment of an adequate therapy. The clinical exam and the laboratory tests did not point out any pathological elements. The native abdominal ultrasound was without pathological modifications, while the contrast-enhanced ultrasonography revealed bilateral vesicoureteral reflux. The renal scintigraphy with DMSA showed impaired renal function on the right side, of 39% with duplicity of the collector system and moderate dilation of the superior pelvis, and normal function of the left kidney. The recommendations consisted in long-term antibiotic prophylaxis, contrast-enhanced ultrasonography once a year and nephrologist consult every 6 months. The particularity of the case consists in diagnosing a bilateral vesicoureteral reflux by contrast-enhanced ultrasonography in a female patient with a history of multiple urinary tract infections, in whom the native renal ultrasound did not point out any pathological elements.